Neuropathic pain: targeting the melatonin MT2 receptor - N. Smith (AOSIS, 2016)
Neuropathic pain affects a large proportion of the population and reduces a person’s ability to perform optimally. In South Africa, there are a host of factors that hinder the correct diagnosis and treatment of neuropathic pain. Patients suffering from neuropathic pain are treated suboptimally with NSAIDS and opioids as first-line therapy. In 2012, a South African guideline on neuropathic pain was released, which stated that opioid therapy should be reserved for last-line treatment only. More recently, melatonin, commonly known as the neurohormone that regulates the circadian rhythm, has come to light as a therapeutic treatment option in the neuropathic pain setting. Early clinical trials showed a link between melatonin and chronic pain, which includes neuropathic pain. The MT2 receptor has also been specifically linked to the control of neuropathic pain and inflammation.